2022
DOI: 10.1037/tmb0000074
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment bystander training effectiveness: Experimentally comparing 2D video to virtual reality practice.

Abstract: Sexual harassment (hereafter SH) is a dysfunctional workplace behavior, resulting in negative outcomes for individuals, work groups, and organizations. Since #MeToo, companies have been innovating to increase the effectiveness of SH training by incorporating new content (e.g., bystander intervention skills) and new technology (e.g., virtual reality, hereafter VR). However, research has yet to determine the best practices or the effectiveness of these new innovations. The present study hypothesizes that SH byst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Regarding male or female non-clinical participants (i.e., community, no previous experience in IPV), gender differences were not analyzed in either of the studies (De Borst et al, 2020;Rawski et al, 2022). However, in De Borst et al (2020), it is stated that it could be interesting to investigate whether for female participants it is easier to place themselves in the victims' shoes than for the male participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding male or female non-clinical participants (i.e., community, no previous experience in IPV), gender differences were not analyzed in either of the studies (De Borst et al, 2020;Rawski et al, 2022). However, in De Borst et al (2020), it is stated that it could be interesting to investigate whether for female participants it is easier to place themselves in the victims' shoes than for the male participants.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the type of intervention, seven studies focused on prevention, and five studies focused on rehabilitation. While most prevention studies focused on increasing assertiveness skills and empathy to prevent being the victim or the offender of IPV or sexual harassment (Ventura et al, 2021;Rowe et al, 2015;De Borst et al, 2020), one study sought to help reduce sexual harassment by training bystanders (Rawski et al, 2022), and another one focused on trying to explore group aggression and bystander behavior through embodiment with a victim of sexual harassment (Neyret et al, 2020). Regarding rehabilitation studies, most were done with the purpose of reducing offenders' risk of IPV or aggressive behavior (Seinfeld et al, 2018;Gonzalez-Liencres et al, 2020;Klein Tuente et al, 2020;Seinfeld et al, 2023), while one study focused on the rehabilitation of sexual violence survivors (Lee and Cha, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VR systems might provide a more objective window. Rawski and her colleagues found that volunteers who watched a sexual-harassment situation in a VR system were more likely than those who watched it on a screen to say that they would intervene indirectly, by creating a distraction or following up with the target later 2 . Rawski suspects that because the VR system felt more authentic, participants had more desire to help despite still being anxious about confronting the perpetrator directly.…”
Section: Delicate Tacticsmentioning
confidence: 99%